2005
DOI: 10.1063/1.1850458
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio potential-energy surfaces for complex, multichannel systems using modified novelty sampling and feedforward neural networks

Abstract: A neural network/trajectory approach is presented for the development of accurate potential-energy hypersurfaces that can be utilized to conduct ab initio molecular dynamics (AIMD) and Monte Carlo studies of gas-phase chemical reactions, nanometric cutting, and nanotribology, and of a variety of mechanical properties of importance in potential microelectromechanical systems applications. The method is sufficiently robust that it can be applied to a wide range of polyatomic systems. The overall method integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
156
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 82 publications
1
156
0
3
Order By: Relevance
“…Neural networks have also been used in combination with QMC to provide information of quantum phase transitions [19][20][21] , topological states 22-25 , manybody localization 21,26 and entanglement properties 27 . Furthermore, neural networks are useful to fit functional forms for potential energy surfaces which are then used in subsequent simulations 28 . In contrast to the situations described above, where DQMC is applied to tight-binding Hamiltonians and the energy scales U, t, T, µ are unambiguously known, in these studies the network is used to avoid complicated and somewhat arbitrary fits to the functional form of the potential energy, allowing for more robust molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks have also been used in combination with QMC to provide information of quantum phase transitions [19][20][21] , topological states 22-25 , manybody localization 21,26 and entanglement properties 27 . Furthermore, neural networks are useful to fit functional forms for potential energy surfaces which are then used in subsequent simulations 28 . In contrast to the situations described above, where DQMC is applied to tight-binding Hamiltonians and the energy scales U, t, T, µ are unambiguously known, in these studies the network is used to avoid complicated and somewhat arbitrary fits to the functional form of the potential energy, allowing for more robust molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…14 Over the past two decades, they have been applied to fit many high-dimensional PESs for isolated molecules and moleculesurface systems. [15][16][17][18][19][20][21][22][23] Recently, we reported a very accurate global PES for the H 2 +OH ↔ H 2 O+H reaction based on ∼17 000 ab initio points calculated at UCCSD(T)-F12/augcc-pVTZ level of theory. 24 Various tests revealed that the new surface is considerably more smooth and accurate than the existing YZCL2 and XXZ surfaces, 25,26 representing the best available potential energy surface for the OH 3 system.…”
mentioning
confidence: 99%
“…17 Then we started to perform NN fitting and carried out extensive quasi classical trajectory (QCT) calculations on the fitted PES to generate more molecular configurations. New data points were selected from generated molecular configurations by using a selection scheme originally proposed by Behler,22,24 and had their ab initio energies calculated, added to the data set.…”
mentioning
confidence: 99%
“…On the other hand, the total number of training structures should be as small as possible not only to avoid time-consuming reference calculations but also to keep the optimization process efficient. A systematic way to generate the training data for systems of arbitrary dimensionality is to employ MD tra-jectories to sample relevant configurations [28,57,76]. First, based on a set of initial training structures a preliminary NN potential is constructed and used to perform MD simulations.…”
Section: Construction Of the Reference Setmentioning
confidence: 99%
“…NNs have been used for about two decades to construct PESs for a number of different systems and several reviews have been published [22][23][24][25]. Most of these NN potentials, however, are restricted to small molecules [26][27][28][29][30][31][32] or small molecules interacting with frozen metal surfaces [33][34][35][36][37][38]. Only a few potentials for higher-dimensional systems exist, which aim to describe the properties of solids [39,40].…”
Section: Introductionmentioning
confidence: 99%